Wintering heifers on bluestem pasture; molasses vs. sorghum grain, soybean meal vs. soybean meal plus beef tallow - Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
In this experiment two feeds were evaluated as possibilities for economically increasing gains on winter pasture. Molasses was self-fed to heifer calves in one pasture and compared with sorghum grain hand fed to heifer calves in another pasture. The dry matter intake was maintained at about the same level by varying the sorghum grain intake to equal molasses consumption. Soybean meal was fed as a source of protein to both lots. A third lot was fed soybean meal with beef tallow added to study beef tallow as a source of energy and to observe its effect on palatability. The beef tallow varied in percentage fed, but the soybean meal fed this lot contained an average of about 10 % tallow. Inedible stabilized bleachable fancy tallow was fed.
Keywords: Beef; Bluestem pasture; Molasses vs. sorghum grain; Soybean meal vs. soybeal meal plus beef tallow